2016
DOI: 10.1515/jas-2016-0011
|View full text |Cite
|
Sign up to set email alerts
|

GC-MS investigation of the chemical composition of honeybee drone and queen larvae homogenate

Abstract: A b s t r a c tHoneybee larva homogenate appears to be underrated and insufficiently explored but this homogenate is an exceptionally valuable honeybee product. Drone larva homogenate is very nutritional due to its high content of proteins, free amino acids, lipids, and carbohydrates. Moreover, the biological characteristics of honeybee larvae indicate the presence of chemical substances that may be pharmacologically active. In spite of the above, the chemical composition of honeybee larva has not gained as mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 13 publications
1
22
0
4
Order By: Relevance
“…These last two bee products are not very known and studied, thus very few literature data regarding their chemical composition is existing at this time (Bărnuţiu et al, 2013, Andriţoiu et al, 2014, Isidorov et al, 2016, and this paper represent a step ahead in the characterization of these products.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…These last two bee products are not very known and studied, thus very few literature data regarding their chemical composition is existing at this time (Bărnuţiu et al, 2013, Andriţoiu et al, 2014, Isidorov et al, 2016, and this paper represent a step ahead in the characterization of these products.…”
Section: Resultsmentioning
confidence: 97%
“…In terms of chemical composition, there are various scientific articles and standards for RJ and Apilarnil, while for queen bee larvae triturate there is no literature data available until now, excepting a study from 2016 (Isidorov et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Bees and their brood can be used directly and are known to be highly nutritious and therefore possibly a potent ingredient in convalescence and health promoting diets [ 83 , 89 ]. Tangsa people of North-East India allow themselves to be stung once a year by a bee “for good health” (Jugli, pers.…”
Section: Major Kinds Of Largely Terrestrial Arthropods Used Therapeutmentioning
confidence: 99%
“…According to research by a number of authors, native DBH contains 70.3-73.6% of moisture, 3.5-3.8% -lipids, 8.12-10% -protein, 38.81% -amino acids, including free ones -8,76%, out of 20 available amino acids, 9 are irreplaceable [4,7,11,19,21]. Carbohydrates are represented mainly by glucose and sucrose; their share reaches 7.88 and 8.22%, respectively [19].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrates are represented mainly by glucose and sucrose; their share reaches 7.88 and 8.22%, respectively [19]. Calculations by Valery A. Isidorov et al showed that this product has a high calorie content -501.4 kcal in 100 g [7].…”
Section: Introductionmentioning
confidence: 99%